2015
DOI: 10.1515/msp-2015-0076
|View full text |Cite
|
Sign up to set email alerts
|

Transparent fluorinate acrylic polyurethane with hydrophobicity obtained by crosslinking of hydroxyl-containing fluoroacrylate copolymer with HDI trimer

Abstract: Hydroxyl-containing fluoroacrylate copolymers with different fluorine and hydroxyl concentrations were synthesized via free-radical solution polymerization. Transparent fluorinated polyurethane (FPU) films were prepared by curing the copolymers with HDI (hexamethylene diisocyanate) trimer. The Fourier transform infrared spectroscopy (FT-IR) results revealed introduction of fluorine both into the copolymer and polyurethane. X-ray photoelectron spectroscopy (XPS) analyses indicated that a gradient concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The absorption band for the NCO stretching of XDI is at around 2260 cm -1 , which can be used to monitor the isocyanate group conversion during polymerization [28]. On the other hand, the characteristic bands of C=O at 1673 cm -1 and NH at 3510-3100 cm -1 were clearly observed in the spectra of the cured sample, which also proved the formation of polythiourethane [28,31]. The absorption at 2540 cm -1 is due to -SH of BES [32].…”
Section: Resultsmentioning
confidence: 85%
“…The absorption band for the NCO stretching of XDI is at around 2260 cm -1 , which can be used to monitor the isocyanate group conversion during polymerization [28]. On the other hand, the characteristic bands of C=O at 1673 cm -1 and NH at 3510-3100 cm -1 were clearly observed in the spectra of the cured sample, which also proved the formation of polythiourethane [28,31]. The absorption at 2540 cm -1 is due to -SH of BES [32].…”
Section: Resultsmentioning
confidence: 85%
“…Figure presents the C1s curves under high‐resolution XPS among the HFBA/WPUs with different ratios of the HFBA chain extenders. The C1s curve of the HFBA/WPU containing polyether diols (as the soft segment) exhibited six obvious peaks at 285.0 eV (CC), 286.4 (CO), 286.8 (COC), 288.0 (OCO), 291.6 (CF 2 ), and 292.0 eV (CF 3 ), among which the OCO was assigned to the urethane carbonyl groups. Figure indicated that the peaks at 290.0 and 292.0 eV did not exhibit noticeable changes when the HFBA content increased, yet the intensity of these peaks had been altered [Figure (b,c)].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the coating's transparency will not be impacted because these nanometer-sized domains are smaller than the visible light wavelength. 18,19 When the surface lubricating layer of the coating is damaged, the antismudge component supply from these nanopools could migrate to the coating surface again to achieve self-compensation of the antismudge function. 20,21 Since 2015, the NP-GLIDE technology has been widely used to functionalize epoxy and polyurethane (PU) coatings due to their excellent wear resistance, flexibility, and transparency.…”
Section: Introductionmentioning
confidence: 99%
“…The low-surface-tension component inside the coating forms microphase separation and generates localized nanodomains that act as “nanopools” of a dewetting agent. In addition, the coating’s transparency will not be impacted because these nanometer-sized domains are smaller than the visible light wavelength. , When the surface lubricating layer of the coating is damaged, the antismudge component supply from these nanopools could migrate to the coating surface again to achieve self-compensation of the antismudge function. , …”
Section: Introductionmentioning
confidence: 99%